2018
DOI: 10.1080/14786451.2018.1448398
|View full text |Cite
|
Sign up to set email alerts
|

Cost-optimal energy performance measures in a new daycare building in cold climate

Abstract: New municipal service buildings must be energy effective, and cost-optimality is one of the criteria for selecting the suitable energy performance improvement measures. A daycare building in a cold climate was studied by means of simulation-based, multiobjective optimization. Using a genetic algorithm, both target energy use and life-cycle cost of the selected measures were minimized. It was found that extensive insulation of the building envelope is not a cost-optimal method to reduce the daycare building ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…The designed delivered energy use in Finnish day care center 2 was 71 kWh/(m 2 •K). Sankelo et al (2018) showed that with the similar initial investment cost it would be possible to reach to much lower energy use and cost optimal levels for day-care centres lie on 35 -40 kWh/(m 2 •K) for buildings with GSHP and 70 -80 kWh/(m 2 •K) for buildings with district heating.…”
Section: Discussionmentioning
confidence: 99%
“…The designed delivered energy use in Finnish day care center 2 was 71 kWh/(m 2 •K). Sankelo et al (2018) showed that with the similar initial investment cost it would be possible to reach to much lower energy use and cost optimal levels for day-care centres lie on 35 -40 kWh/(m 2 •K) for buildings with GSHP and 70 -80 kWh/(m 2 •K) for buildings with district heating.…”
Section: Discussionmentioning
confidence: 99%
“…Sankelo et al [16] showed that a highly insulated building envelope is not a cost-optimal energy performance measure; rather, improvement of the ventilation system, onsite use of solar energy, and employing a light control strategy are preferable ways of improving the building energy performance. Michelsson et al [17] analysed alternative energy-saving design concepts for a typical, new, detached house design in Finland and showed that the payback period is the shortest for air source heat pumps.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Finland, where has similar climatic condition with Norway, the energy use variation of both heating and electricity can be high up to 10-fold between the least and most energy-efficient daycare buildings [16]. It proves important and meaningful to develop average and representative energy profile for one building type for future energy planning.…”
Section: Comparison With Similar Building Type In Other Areasmentioning
confidence: 99%